Role of rotational inertia for collective phenomena in active matter. Issue 40 (6th October 2022) - Caprini, Lorenzo; Gupta, Rahul Kumar; Löwen, Hartmut
Abstract : We investigate the effect of rotational inertia on the collective phenomena of underdamped active systems, showing that the increase of the moment of inertia favors motility induced phase separation and enhances spatial velocity correlations. Abstract : We investigate the effect of rotational inertia on the collective phenomena of underdamped active systems and show that the increase of the moment of inertia of each particle favors non-equilibrium phase coexistence, known as motility induced phase separation, and counteracts its suppression due to translational inertia. Our conclusion is supported by a non-equilibrium phase diagram (in the plane spanned by rotational inertial time and translational inertial time) whose transition line is understood theoretically through scaling arguments. In addition, rotational inertia increases the correlation length of the spatial velocity correlations in the dense cluster. The fact that rotational inertia enhances collective phenomena, such as motility induced phase separation and spatial velocity correlations, is strongly linked to the increase of rotational persistence. Moreover, large moments of inertia induce non-monotonic temporal (cross) correlations between translational and rotational degrees of freedom truly absent in non-equilibrium systems.